2011
DOI: 10.1071/he11128
|View full text |Cite
|
Sign up to set email alerts
|

Injuries across adolescence: an investigation using the Extended Adolescent Injury Checklist (E-AIC)

Abstract: A broad variety of injuries, occurring in context of multiple risk as well as normative behaviours, were reported by adolescents in both school and ED settings, and were captured by the E-AIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Hammig et al [8] reported in the United States National Longitudinal Study of Adolescents Health that involvement in fights was associated with injuries among the adolescents. In a study of Australian adolescents reported by Chapman et al [9] the commonest among adolescents arising from sports, followed by fights. Alcohol use was most frequently reported to be associated with interpersonal violence injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Hammig et al [8] reported in the United States National Longitudinal Study of Adolescents Health that involvement in fights was associated with injuries among the adolescents. In a study of Australian adolescents reported by Chapman et al [9] the commonest among adolescents arising from sports, followed by fights. Alcohol use was most frequently reported to be associated with interpersonal violence injuries.…”
Section: Introductionmentioning
confidence: 99%